2022
DOI: 10.1038/s41419-022-05065-4
|View full text |Cite|
|
Sign up to set email alerts
|

Semaphorin 5A suppresses ferroptosis through activation of PI3K-AKT-mTOR signaling in rheumatoid arthritis

Abstract: Abnormal activation of synovial fibroblasts (SFs) plays an important role in rheumatoid arthritis (RA), the mechanism of which remains unknown. The purpose of our study is to comprehensively and systematically explore the mechanism for Semaphorin 5A-mediated abnormal SF activation in RA. Here, we found that Semaphorin 5A levels were significantly higher in synovial fluid and synovial tissue from RA patients compared with osteoarthritis patients. We further found that the mRNA level and protein abundance of Ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…The Annexin V + / PI– fraction represents apoptotic cells while Annexin V + / PI + may include both late apoptotic and necrotic cells. Our data, together with previous studies [ 39 , 56 , 58 61 ], demonstrated a subset of cells with Annexin V-/ PI + in ferroptosis, detected by Annexin V/PI assay, and our subsequent results further verified the co-treatment-induced ferroptosis. However, some studies indicated that cells with Annexin V + / PI + represented the initiation process of ferroptosis, which needs to perform time-course experiments to elucidate.…”
Section: Discussionsupporting
confidence: 89%
“…The Annexin V + / PI– fraction represents apoptotic cells while Annexin V + / PI + may include both late apoptotic and necrotic cells. Our data, together with previous studies [ 39 , 56 , 58 61 ], demonstrated a subset of cells with Annexin V-/ PI + in ferroptosis, detected by Annexin V/PI assay, and our subsequent results further verified the co-treatment-induced ferroptosis. However, some studies indicated that cells with Annexin V + / PI + represented the initiation process of ferroptosis, which needs to perform time-course experiments to elucidate.…”
Section: Discussionsupporting
confidence: 89%
“…MDA is a final product of lipid peroxidation, which shows a positive correlation with ferroptosis [ 21 ]. The MDA concentration in GC cells was measured by the thiobarbituric acid method using a cell MDA assay kit (A003-4, Jiancheng Bioengineering Institute, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the regulation of MAPK and JNK/ERK signaling pathways also plays a protective role ( Ning et al, 2021 ; Zhu et al, 2022 ). Recently, it was found that Neferine can alleviate LPS-induced oxidative stress through AKT/mTOR signaling pathway ( Qi et al, 2021 ), and it was reported that ferroptosis could be attenuated by activating AKT/mTOR signaling pathway ( Cheng et al, 2022 ), which provides a new idea for our study. The AKT/mTOR signaling pathway is involved in the development of multiple diseases.…”
Section: Discussionmentioning
confidence: 97%